Prevalence of pneumonia and its determinant factors among under-five children in Gamo Zone, southern Ethiopia, 2021 - Solomon, Yerukneh; Kofole, Zelalem; Fantaye, Tewodros; Ejigu, Solomon (Frontiers in Pediatrics, 2022)
Background: Pneumonia; which is a form of acute lower respiratory tract infection affects the lung parenchymal and destructs alveolar air space. Pneumonia is the leading cause of morbidity and mortality in under-five children. It was estimated that pneumonia kills 900,000 under five children each year worldwide. Approximately 172 deaths per 1000 live births occur in sub-Saharan African countries; with the major cause of pneumonia. The study aimed to assess the prevalence and determinant factors of pneumonia in under five children, Arba Minch town, Southern Ethiopia. Methodology: Institutional cross-sectional study was employed. A total of 239 child-caregiver pairs were included. Data were collected by trained nurses using semi structured questionnaire. The collected data were checked for completeness, coded and entered into EPI data version 4.6. and exported to SPSS version 25 for analysis. Results were reported by mean, frequency, percentiles. Logistic regression was employed to assess statistically significant predictors of pneumonia. Variables with a P-value of < 0.05 were considered as statistically significant factor of pneumonia. Result: The prevalence of pneumonia in the study area was 30%. Among factors assessed, Place of food cooking inside living room (AOR=5.79, 95% CI: 2.47, 13.58), non-exclusive breast feeding (AOR=3.26, 95% CI: 1.42, 7.52), Vitamin A supplementation status (AOR=5.62, 95% CI: 2.65, 11.94) and Vaccination status (AOR=3.59, 95% CI: 1.49, 8.66) were significantly associated with the occurrence of pneumonia in under five children. Conclusion: This study showed that the prevalence of pneumonia was relatively higher in Arba Minch town compared to studies’ reports from other parts of the country. Place of food cooking, non-exclusive breast feeding, vitamin A supplementation status and vaccination status of children were significant factors of pneumonia among under-five children. Enhancing care givers/mothers awareness on predicted factors needed to reduce the incidence of childhood pneumonia and to increase enhanced children’s quality of health.